Prioritizing public interest in public relations: Public interest relations. (September 2019) - Brunner, Brigitta R.; Smallwood, Amber M. K.
Though early public relations leaders set up serving the public interest as an unquestionable role for public relations, contemporary public relations practice and scholarship have focused on organizations' goals and activities giving little attention to the public interest. We put forth Public Interest Relations (PIR), which resituates the public interest as central to the work in and scholarship of public relations. PIR recognizes public relations practitioners have a civic duty to create spaces for dialogue; encourage and listen to diverse viewpoints; offer honest analysis and synthesis toward recommendations that advocate for the public interest; and act in the public interest, while also advancing organizational goals. Because organizations may engage in PIR in different ways, a three-category PIR continuum is offered. When PIR is practiced, we propose trust will grow, community will be built, and goodwill will be fostered.